Lift The Flap Storybook to Grow and Raise Awarness about Sugar Intake in Early Chilhood and Their Parents - Jayanti, Diana Dwi; Muttaqin, Zainal; Leksana, Dinar Mahdalena (Jurnal Midpro, 2020)
This research entitled Lift The Flap Storybook to Grow and Raise Awarness about Sugar Intake in Early Chilhood and Their Parents. The purpose of this research is to develop a media to grow and raise understanding of the balanced proportion of sugar intake in early chilhood and their parents. The expected benefit from this research is to provide educational media that is easy to use and understand, and does not harm children, besides that it can instill awareness of healthy living from an early age and an understanding of the importance of balanced food intake by parents for family members. This research is a development research (R & D) using a qualitative approach as a data collection and analysis process. The subject of this research involved 20 parents who have early childhood as participants/media users and also three experts in the field of early childhood education, graphic design, and language as validators. The results of this research showed that: a) of the 20 participants who were involved in the study, 9 families had a pattern of excess sugar consumption, b) the results of media feasibility validation by experts show that the content, design and language in the media are in the good and very good categories, c) the results of trials related to the effectiveness of the use of media by users (parents and children) show that there is an increase in awareness as indicated by changes in sugar consumption patterns in children and parents (families) which initially tend to be more balanced.Â Keywords: Lift The Flap Storybook, Sugar Intake Awareness, Earlychilhood and Parents.